Safely correct hyponatremia with continuous renal replacement therapy: A flexible, all‐purpose method based on the mixing paradigm. Issue 1 (5th January 2023) - Chen, Sheldon; Yee, Jerry; Chiaramonte, Robert
Abstract: Treating chronic hyponatremia by continuous renal replacement therapy (CRRT) is challenging because the gradient between a replacement fluid's [sodium] and a patient's serum sodium can be steep, risking too rapid of a correction rate with possible consequences. Besides CRRT, other gains and losses of sodium‐ and potassium‐containing solutions, like intravenous fluid and urine output, affect the correction of serum sodium over time, known as osmotherapy. The way these fluids interact and contribute to the sodium/potassium/water balance can be parsed as a mixing problem. As Na/K/H2 O are added, mixed in the body, and drained via CRRT, the net balance of solutes must be related to the change in serum sodium, expressible as a differential equation. Its solution has many variables, one of which is the sodium correction rate, but all variables can be evaluated by a root‐finding technique. The mixing paradigm is proved to replicate the established equations of osmotherapy, as in the special case of a steady volume. The flexibility to solve for any variable broadens our treatment options. If the pre‐filter replacement fluid cannot be diluted, then we can compensate by calculating the CRRT blood flow rate needed. Or we can deduce the infusion rate of dextrose 5% water, post‐filter, to appropriately slow the rise in serum sodium. In conclusion, the mixing model is a generalizable and practical tool to analyze patient scenarios of greater complexity than before, to help doctors customize a CRRT prescription to safely and effectively reach the serum sodium target. Abstract : The treatment of chronic hyponatremia by CRRT is complicated, but it can be modeled as a calculus mixing problem. The differential equation's solution corroborates the science of osmotherapy and shows us how to use the various CRRT settings to safely correct hyponatremia.